Pemanfaatan Linguistik Interdisipliner dalam Kajian Teks Keagamaan - Nuril Hidayah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Change is one of human being’s nature, so as of language as a product of interaction between them. In turn, it’s hard for two persons of different space or time to infer same meaning even from one same language. The same case occurs in Islamic religious text (al-Qur’an) which use Arabic language as a media to deliver its message. The changes in language has produced meaning gaps between the text and contemporary audiens (reader). Attempts have been made to build a bridge between those territorial and temporal meaning gaps including utilizing linguistics to figure out the authentic meaning, ranging from general linguistics until interdisciplinary ones, whether as a perspective or a method. But the last has not yet been used vastly in religious text studies. This article attempts to make a brief review about the use of interdisciplinary linguistics, namely anthropolinguistics in those studies and to propose some ideas about how to use them as a perspective and or a method.